(3GdafOb aj CMcGe GdHfObs
(3ChdgG (B:s
(3CeG HYO aEf GdEeGe GdaGVd GdfajS GdeYQha HGHf GdHbGd Ufa cJGH GdebJQM ai GdeUWdM s
(3BNQgG (B:s
(3hJYjf GdCUfGa ai hbJ GdMed bhdkG hGMOkG hGddg JYGdi CYde hgPG BNQ eG hLOfGg ef cJGH GdafOb ai CMcGe GdHfOb s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs